Case Report: Somatic malignancy classified as Wilms tumor arising within an immature teratoma - Emily Muñoz; Emily Muñoz; Emily Muñoz; Cyrus Washington; Cyrus Washington; Cyrus Washington; Pasquale Benedetto; Pasquale Benedetto; Ali Saad; Oleksandr N. Kryvenko; Oleksandr N. Kryvenko; Oleksandr N. Kryvenko; et al. (Frontiers in Oncology)
Nongeminomatous germ cell tumors (NGGCTs) are aggressive malignancies known for their rapid metastatic potential. Teratomas, a subtype of NGGCTs, can be classified as either mature (benign) or immature (malignant). Immature teratomas carry a higher metastatic risk than mature teratomas due to their embryonic-like tissue composition. Intracranial teratomas are rare in nature and can develop secondary malignancies, such as Wilms tumors. We report the case of a 70-year-old man with a history of prostate cancer who presented with neurological symptoms and was diagnosed with a Wilms tumor arising from an immature teratoma. A heterogenous morphology, including squamous, cartilaginous, and neural differentiation, was revealed upon surgical resection. Despite interventions, the patient experienced rapid disease progression and eventually passed away in hospice care 7 months after the initial diagnosis. This case highlights the complexity of diagnosing and managing NGGCTs, particularly when secondary malignancies arise. Ultimately, it underscores the need for careful diagnosis and precise therapeutic strategies to manage these tumors.